Hippotherapy on postural balance in the sitting position of children with cerebral palsy – Longitudinal study. (1st February 2020) - Moraes, Andréa Gomes; Copetti, Fernando; Ângelo, Vera Regina; Chiavoloni, Luana; de David, Ana Cristina
ABSTRACT: Purpose : To verify the effects of 12, 24, 36 hippotherapy sessions over time on postural balance while sitting in children with cerebral palsy as well the effects of treatment after one interruption period of 45 days. Methods : Hippotherapy program with a twice-weekly treatment with a total of 13 children aged 5–10 years old. Measurements of postural balance during sitting were performed using the AMTI AccuSway Plus platform. Results : There was a statistically significant reduction in mediolateral and anteroposterior sway after the first 12 hippotherapy sessions, and further significant sway reduction occurred as the treatment progressed. Changes in the center of pressure displacement velocity variable began to occur after 24 sessions. Conclusion : Seated postural balance improved in children with cerebral palsy, as evidenced by lower COP displacement, particularly after a greater number of sessions. After the last evaluations, when completing 36 sessions of hippotherapy, it was verified that the improvements to the postural balance continued to occur. Therefore, further studies with a longer treatment period may help to clarify if, at some point, there is stabilization in the improvement of postural balance. Furthermore, it is important to analyze the impact of hippotherapy on functional activities over time.